Hegemony and Representation of Black Actresses in The Little Mermaid (2023) - OK Dedi Arwansyah; Muhammad Rasyad Ghazali Saraan; Armansyah Matondang; Eka Fatmawati (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This article reviews the debate and impact of Halle Bailey's selection as Ariel in the live-action film "The Little Mermaid" (2023) on racial representation and inclusivity in the Hollywood film industry. Motivated by the growing attention to the representation of minority groups in mass media, this analysis explores the hegemony of white culture and the way racial representation is manifested in film production. Based on Antonio Gramsci's theory of hegemony and the concept of representation, this study explores the public response to Bailey's casting, as well as its impact on traditional narratives and attempts to deconstruct existing power structures. Through an approach to cultural studies and racial-critical theory, this article aims to provide a deeper understanding of the dynamics of power and representation in mass media and highlight steps towards a more inclusive and equitable film industry. In conclusion, the selection of Halle Bailey as Ariel not only marks an important step in stimulating discussion about diversity in popular culture, but also a concrete step towards a more inclusive and representative film industry.